2011
DOI: 10.1111/j.1399-3038.2011.01232.x
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of GINA criteria and childhood asthma control test on the determination of asthma control

Abstract: Consistency between GINA and C-ACT is not as to be expected. Using only one method for determining the control level of asthma does not seem to be reliable and accurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 26 publications
0
14
1
5
Order By: Relevance
“…Another factor that might have contributed to our findings is the fact that c-ACT-based asthma control was reported to have <30% non-compatibility with GINA guideline base asthma control. Although the c-ACT is a validated questionnaire [18] and it is widely used for healthcare and research purposes, it seems to overestimate asthma control levels in children with poor asthma control or poor symptom perception [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that might have contributed to our findings is the fact that c-ACT-based asthma control was reported to have <30% non-compatibility with GINA guideline base asthma control. Although the c-ACT is a validated questionnaire [18] and it is widely used for healthcare and research purposes, it seems to overestimate asthma control levels in children with poor asthma control or poor symptom perception [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have shown a high level of agreement between both tests and GINA criteria . Only one study found a significant discrepancy between C‐ACT and GINA levels of control . It was hypothesized that this discrepancy was due to the fact that GINA levels are based on frequency of symptoms and on pulmonary function tests, whereas the C‐ACT score is determined by the severity of symptoms only.…”
Section: Gold Standard Of Asthma Controlmentioning
confidence: 99%
“…This might be explained by the fact that people tend to adjust themselves in the middle range (known as the error of central tendency). Furthermore, patients have different perceptions of their level of control than their doctor …”
Section: Discussionmentioning
confidence: 99%